Service Process Improvement Using Lean Service Management in Driving License Administration - Choirunisa Octavia; Nurullaily Kartika (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
The service process for issuing Driving Licenses (SIM) at Unit X continues to face long queues and extended waiting times, negatively affecting the effectiveness of public service delivery. This study aims to analyze the service value stream and identify waste using a lean service approach. The research adopts a qualitative methodology through observation, interviews, and process analysis employing Value Stream Mapping (VSM), Process Activity Mapping (PAM), and a Fishbone Diagram. The results of the Current State VSM indicate a total service time of 85.91 minutes. The main sources of waste are waiting and defects, particularly during the theory and practical examination stages. Based on the proposed improvements, the Future State Mapping reduces the total lead time to 57.65 minutes, with value-added processing time of 45.15 minutes, thereby significantly improving service efficiency. These findings demonstrate that implementing lean service effectively reduces waste, streamlines service flow, and enhances the quality and speed of the driving license issuance process.